Non-fungible tokens and factors affecting their pricing in a meta synthesis method - Zahra Dehghani FiroozAbadi; Zohreh Aref manesh (راهبرد مدیریت مالی)
Non-fungible tokens are known as unique digital assets that are stored in the blockchain. Their non-fungibility makes them different from other crypto assets. Therefore, their pricing is different from the pricing of similar tokens The purpose of this research is to identify the basic characteristics and better understanding of the factors affecting the pricing of these tokens in meta synthesis method Which is done by using Sandelowski's seven steps and by searching the title, abstract and main text of the sources in the databases that were provided until September 2023. In total, among the 86 sources found, 35 researches reached the content acceptance stage. This research is one of the first researches that has identified the factors affecting the pricing of non- fungible tokens, while so far these factors have not been presented using the meta synthesis method. The results indicate that 30 factors are effective in the pricing of Non-fungible tokens, which are categorized into six components and two main groups. The validity of this research has been explained by explaining the steps and using the critical assessment skills program method, and the reliability was measured and confirmed using the intraclass correlation method.